Hubungan Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) pada Mata Pelajaran Fikih (Kitab Fathul Qarib) terhadap Hasil Belajar Siswa Kelas VIII di PPTI Tarusan Kamang - Abdul Rahman; Bambang Trisno (Lembaga Yasin AlSys, 2026)
Low student learning outcomes in Fiqh have received attention in various studies, but research specifically analyzing the relationship between the implementation of the Cooperative Integrated Reading and Composition (CIRC) model and Fiqh learning outcomes through the study of Kitab Fathul Qarib in an Islamic boarding school setting remains limited. This study aimed to analyze the relationship between the implementation of the CIRC learning model and the learning outcomes of eighth-grade students at PPTI Tarusan Kamang. The study employed a quantitative approach with a correlational design involving 35 students selected as the sample through total sampling. Data were collected using a questionnaire on the implementation of the CIRC model, a learning outcomes test, observation, and documentation. The data were analyzed using descriptive statistics, a normality test, a linearity test, and Pearson Product-Moment correlation with the assistance of IBM SPSS Statistics 25. The results showed that the implementation of the CIRC model had a positive and significant relationship with students’ learning outcomes (r = 0.651; p < 0.05), with a coefficient of determination of 42.4%. These findings indicate that the better the implementation of the CIRC model, the higher the students’ Fiqh learning outcomes. This study confirms the importance of implementing active, collaborative, and student-centered learning to improve Fiqh learning outcomes. Theoretically, these findings extend the literature on cooperative learning in Islamic education, while practically, the results can serve as a basis for teachers to develop more participatory and effective learning of Kitab Fathul Qarib in Islamic boarding school settings.